(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This paper is an attempt to show how teachers have been trying to achieve the standards given by the National Universities Commission (NUC) for the graduation of distributive education teachers. However, since the emergence of the use of information technology in Nigerian business transactions, emphasis should have shifted to computerbased pedagogy to replace standards driven and teacher centred curricula. This paper argues that student-centred approach by which students select goals, timelines, assessment and have much more computer based practicals will motivate students much more, offer them more opportunities to carry out their own projects of study and prepare them better for selfemployment. The paper recommends various measures (such as workshops for business education teachers and professional accreditation visitation of university teachers) before reaccreditations. Recognition for teachers that have ICT abilities to facilitate effective and qualitative distributive teacher education in Nigeria, will help to provide quality assurance.